Limiting factors on the global distribution of horseshoe crabs - John, Akbar; Yunus, Kamaruzzaman (IIUM Press, 2011)
There are at least four large-scale, global, environmental parameters that, spatially and temporally, set limits on the distribution of horseshoe crabs. Of these, continental geomorphology and temperature regimes are two major constraints on the wide spread distribution of horseshoe crabs. Basically, the continental shelves define the areas available to horseshoe crabs while low temperatures limit their northern most occurrences. Tidal types and benthic currents also play a role in the distribution of horseshoe crabs.